Resolving different presynaptic activity patterns within single olfactory glomeruli of Xenopus laevis larvae - Rodi Topci (Nature Portfolio, 2021)
Abstract Olfactory sensing is generally organized into groups of similarly sensing olfactory receptor neurons converging into their corresponding glomerulus, which is thought to behave as a uniform functional unit. It is however unclear to which degree axons within a glomerulus show identical activity, how many converge into a glomerulus, and to answer these questions, how it is possible to visually separate them in live imaging. Here we investigate activity of olfactory receptor neurons and their axon terminals throughout olfactory glomeruli using electrophysiological recordings and rapid 4D calcium imaging. While single olfactory receptor neurons responsive to the same odor stimulus show a diversity of responses in terms of sensitivity and spontaneous firing rate on the level of the somata, their pre-synaptic calcium activity in the glomerulus is homogeneous. In addition, we could not observe the correlated spontaneous calcium activity that is found on the post-synaptic side throughout mitral cell dendrites and has been used in activity correlation imaging. However, it is possible to induce spatio-temporal presynaptic response inhomogeneities by applying trains of olfactory stimuli with varying amino acid concentrations. Automated region-of-interest detection and correlation analysis then visually distinguishes at least two axon subgroups per glomerulus that differ in odor sensitivity.